Green Human Resource Management Dan Organizational Identification Untuk Meningkatkan Green Innovative Work Behavior Karyawan UKM Sarung Tenun DAZ Di Gresik - Dimas Faisal Lazim; Amiartuti Kusmaningtyas (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2024)
DAZ Woven Sarong UKM in Gresik is a company which operates in the textile sector in the form of sarong clothing produced using traditional looms which to this day still maintains the quality and cultivates traditional crafts in the form of woven sarongs. The aim of this research is to determine the influence of Green Human Resource Management and Organizational Identification to improve Green Innovative Work Behavior of DAZ Sarong Tenun UKM employees in Gresik. The population of this study is 46 employees of DAZ Woven Sarong UKM in the production department. Sampling in this research the author used a saturated sample where all members of the population were used as research samples. This research is quantitative research to determine the relationship between the independent variable and the dependent variable. The results of this research show that the Green Human Resource Management variable has a significant influence on Organizational Identification, the Green Human Resource Management variable has a significant influence on Green Innovative Work Behavior and the Organizational Identification variable has a significant influence on Green Innovative Work Behavior. And the mediating variable Z can be said to be successful in mediating and being significant between variables X and Y. Based on the results of the t test on the variable , Based on the results of the t test on the variable Based on the results of the t test on the Z-Y variable, it was obtained that the t count was 11.150 which was greater than the t table of 2.016 with a significant value of 0.000 < 0.05, so H0 was rejected and H1 was accepted, which means that the Organizational Identification variable had a positive and significant influence on the Green Innovative Work Behavior variable.